2020
DOI: 10.1002/2211-5463.12864
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor 4 expression is correlated with the occurrence and prognosis of gastric cancer

Abstract: Gastric cancer (GC) is a common tumor with a low 5‐year survival rate. The chemokine receptor 4 (CXCR4) protein contributes to the progression and prognosis of GC, but the relationship between CXCR4 and immune infiltration, somatic copy number alteration (SCNA), tumor purity, tumor mutation burden (TMB), cytolytic activity (CYT), and drug sensitivity in GC is poorly understood. This study aimed to systematically explore the role of CXCR4 in GC. Microarray and RNA‐seq data were collected from the Gene Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The link between inflammation and GC has been confirmed in many experiments [55]. For example, inflammation-related factors, consist of T lymphocytes, macrophages, cytokines, and pro-inflammatory chemokines, can promote the development of HP related GC [48,56]; Inflammatory fraction is associated with the prognosis of GC [57]; In addition, amplification of inflammatory response can advance the occurrence of GC in the animal model [58]. The above results are consistent with our idea inflammation related gene TREM2 can affects the malignant phenotype of gastric cancer.…”
Section: Discussionmentioning
confidence: 89%
“…The link between inflammation and GC has been confirmed in many experiments [55]. For example, inflammation-related factors, consist of T lymphocytes, macrophages, cytokines, and pro-inflammatory chemokines, can promote the development of HP related GC [48,56]; Inflammatory fraction is associated with the prognosis of GC [57]; In addition, amplification of inflammatory response can advance the occurrence of GC in the animal model [58]. The above results are consistent with our idea inflammation related gene TREM2 can affects the malignant phenotype of gastric cancer.…”
Section: Discussionmentioning
confidence: 89%
“…SCNA of GYPC was downregulated in various immune cells, and arm-level gain of GYPC was associated with neutrophils and dendritic cells ( Figures 5D,E ). CXCR4 was related to altered immune cells, which can affect the prognosis of gastric cancer ( Li et al, 2020 ). A previous study showed that CXCR4 was upregulated in naive CD4+ and CD8+ T cells and CD4+ central memory T cells, which have a crucial role in modulating immune dysfunction ( Ramonell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical investigations have indicated the significance of the aberrant expression of chemokine receptors in GC, including copy number changes or upregulation of chemokine receptors mRNA. In recent years, several cancer parameters, such as immune infiltration, somatic copy number alterations (SCNA), tumor mutation burden (TMB), tumor purity, cytolytic activity (CYT), and drug sensitivity have been reported to be prognostic factors and potential therapeutic markers for various cancers, including GC [ 44 , 45 ]. There was a statistically significant correlation between CXCR4 levels and TMB, CYT, tumor purity, tumor immune infiltration, and drug sensitivity.…”
Section: Chemokines In Gastric Cancermentioning
confidence: 99%
“…There was a statistically significant correlation between CXCR4 levels and TMB, CYT, tumor purity, tumor immune infiltration, and drug sensitivity. Moreover, elevated CXCR4 expression can affect the resistance of cancer cells to drugs [ 44 ]. What is more, a possible link between tumor immunity and aberrant expression of CCR4 in GC cells has been proved [ 46 ].…”
Section: Chemokines In Gastric Cancermentioning
confidence: 99%